OPTIMASI DISTRIBUSI AIR IRIGASI MELALUI SISTEM GOLONGAN (STUDI KASUS DAERAH IRIGASI RONGKONG SELUAS 27.000 HA) - Rifai, Muji; Wahyudi, Agus Hari (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2024)
The utilization of river water to support activities in the agricultural sector includes constructing water structures that function to channel or supply water to rice fields through weirs. The water required for rice fields is referred to as irrigation water demand. The amount of water needed in irrigated areas varies, necessitating a water distribution management system, one of which involves creating a crop planting schedule with a technical/rotational system, ensuring the water balance of an irrigation area is well managed. The aim of this research is to achieve the most efficient planting and water distribution plan for an irrigation area, considering the water balance as an indicator of the water management system in fulfilling irrigation water needs. The method used involves comparing the water balance of irrigation areas where water is supplied using a rotational system versus without. The research results show that the appropriate cropping pattern for an irrigation area of more than 25,000 hectares (ha) is to use a rotational system. For the Rongkong Irrigation Area (DI) with a size of 27,947 ha, it is divided into two groups: Group 1 includes: Rongkong Right Irrigation Area with 4,198.38 ha and Rongkong Left Irrigation Area with 6,497.56 ha; Group 2 includes: Rongkong Right Irrigation Area with 7,501.22 ha and Rongkong Left Irrigation Area with 9,749.22 ha. Before using the rotational system, a water deficit occurred in the first week of October, amounting to 0.22 m³/second. However, after implementing the rotational system, the water balance in the Rongkong Irrigation Area no longer showed any water demand deficit.